HUBUNGAN SUPPORT ORANG TUA DENGAN EKSPLORASI DAN KOMITMEN AREA PEKERJAAN - Sulisworo Kusdiyati (SCHEMA (Journal of Psychological Research), 2009)
One importan task must be achieved by late adolescent is achieving ego identity in almost all area of life, mainly in vocational area/domain. In fact, most undergraduated students of Psychology Departement in Bandung Islamic University didn’t have any certain description about their career planning. They also showed little effort in exploring career informations. They came from the family background that parents didn’t urge them to think about their career planning before they had finished their study.This research is on “The Correlation between the Parent’s Support with The Exploration and The Commitment in Vocational Domain”. The aim of this research is to clarify the role of parent’s support in identity building of late adolescent in vocational domain. The building identity of late adolescent is studied through exploration and commitment done by late adolescent in the planning work.This research is a correlational research which done to study a correlation between the parent’s support with the exploration and commitment in vocational domain. The research subject of this study were undergraduated students from Psychology Departement in Bandung Islamic University. By using the Purposive Sampling technique, be gained 91 students which suitable with the criterias. The data are collected by using questionnaires for parent’s support, exploration of vocational domain and commitment.The data gained are analyzed by Spearman Rank Order Coefficient of Correlation. The result are : 1) there is a significant correlation between parent’s support with the exploration (rs = 0.308, p = 0.002) there is a significant correlation between parent’s support with the commitment (rs = 0.355, p = 0.000). The result of this research also showed there is a significant correlation between the emotional support with the exploration (rs = 0.309, p = 0.001), esteem support with the exploration (rs = 0.255, p = 0.007), informational support with the exploration (rs = 0.331, p = 0.001), tangible support with the exploration (rs = 0.184, p = 0.040). These results showed that the emotional support, esteem support, informational support and tangible support contribute positively to the exploration in vocational domain. The informational support gave the most contribution for the exploration (d = 11%), followed by the emotional support (d = 9.5%), esteem support ( d= 6.5%) and tangible support (d = 3.38%).Also, there is a significant correlation between the emotional support with the commitment (rs = 0.313, p = 0.001), esteem support with the commitment (rs = 0.336, p = 0.001), informational support with the commitment (rs = 0.382 , p = 0.000), and between the tangible support with the commitment (rs = 0.293, p = 0.002). These showed that the emotional support, esteem support, informational support and tangible support contribute positively to the commitment in vocational domain. The informational support gave the most contribution to the commitment (d = 14.6 %), followed by esteem support (d = 11.3%), emotional support (d = 9.7) and tangible support (d = 8.6%).It can be concluded that parent’s support contributes positively to the exploration and the commitment in vocational domain.